Effects From Dietary Addition of Sargassum sp., Spirulina sp., or Gracilaria sp. Powder on Immune Status in Broiler Chickens - Al-Khalaifah, Hanan S.; Al-Nasser, A.; Surrayai, T. (Frontiers in Veterinary Science, 2022)
Algae are innovative and significant nutrient sources with various health benefits when used as additives in animal feed. The study aims to examine the effect of different inclusions of Sargassum sp., Spirulina sp., and Gracilaria sp. on the immune response of broiler chickens, as measured by the cellular immune response, humoral immune response, intestinal microbial counts, hindgut acidosis, and hematological measures. Here is a list of the seven experimental treatments (TRT). TRT 1 was the control group without algae; TRT 2 was supplemented with Sargassum sp. at 1% of the diet; TRT 3 with Sargassum sp. at 2% of the diet; TRT 4 with Spirulina sp. at 5% of the diet; TRT 5 with Spirulina sp. at 7.5% of the diet; TRT 6 with Gracilaria sp. at 0.5% of the diet; and TRT 7 Gracilaria sp. at 1% of the diet. Each treatment involved five replicates with 17 broiler chickens each, and the analyses were triplicated. The results showed that including algae in the feed ration of broiler chickens induces a higher cellular response than the control group, represented by T-cell response in the wattle area (P = 0.037). Sargassum sp. at 1 and 2% enhanced IgA antibody titers significantly and Gracilaria sp. at 5% enhanced IgY antibody titers, P = 0.045 and P = 0.030, respectively. All algal inclusions inhibited the growth of Salmonella sp. and improved LAB counts in the intestine of broilers, excepting the Gracilaria sp. at 0.5%, where LAB counts were similar to the control group. The E. coli counts decreased numerically but not significantly. Blood lymphocytes were enhanced while WBC and heterophils were decreased as a results of algal inclusions. In conclusion, supplementing broiler chickens with algae could enhance their cellular and humoral immune status and promote healthy microflora in their guts.